ASSESSMENT OF DIFFERENT ORGANIC MATTERS ON ANTIOXIDATIVE ENZYME ACTIVITIES AND NUTRITIONAL COMPONENTS UNDER SALT STRESS IN SALAD ROCKET (ERUCA SATIVA) - S. Kusvuran1; S. S. Ellialtioglu (Journal of Animal and Plant Sciences, 2021)
Salad rocket (Eruca sativa), which is becoming increasingly important, comprises a wide variety of phytochemicals that promote health, such as carotenoids, fibers, glucosinolates (GLs), polyphenols, and ascorbic acid (AsA). Variations in the nutritional components of a rocket cultivar and the effects of different organic matter on biochemical changes under salt stress were examined herein. The response of salad rocket (Eruca sativa.) to applications of farmyard manure, humic acid, or vermicompost, as well as water irrigation salinity at 8 dS m-1 was evaluated under greenhouse conditions using plastic pots containing 12 L of loamy sand. For each experiment, 5 treatments were performed, as follows: 1) control [C: NaCl-free], 2) salt treatment [S: irrigation with solution contained 8 dS m-1], 3) salt treatment + cow manure [SM: irrigation with solution contained 8 dS m-1 + farmyard manure 136 g pot–1], 4) salt treatment + HA [SH: irrigation with solution contained 8 dS m-1 + 100 ppm HA], 5) salt treatment + vermicompost (worm casting) [SV: irrigation with solution contained 8 dS m-1 EC + 13.6 mg pot–1]. The experimental treatments were arranged in a randomized plot design with four replicates. At the experiment’s conclusion, the malondialdehyde (MDA), total phenolic, flavonoid, AsA, total GLs contents, and antioxidative enzyme activities [ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR), and superoxide dismutase (SOD)] were determined in the rocket leaves. The results revealed that the salt stress caused decreased photosynthetic pigments like total chlorophyll (Chl), Chl-a, Chl-b, and carotenoid contents, as well as total the GLs and phenolic contents, while total flavonoid, AsA, and SOD, CAT, APX, and GR activities showed an increase. The organic matter applications provided tolerance at different levels, and following the aforementioned procedures, there were significant increases (19%–134%), but the MDA content was reduced by 47%. Moreover, the application of organic matter increased the total GLs and antioxidative enzyme activities of APX, CAT, GR, and SOD under salt stress (21-424% increase). The results supported the application of organic matter to increase the defense system of rocket plant, enabling it to tolerate the negative effects induced by salinity. In addition, these applications contributed to the antioxidative defense system components in salad rocket.
Keywords: Antioxidative enzyme activities; Eruca sativa; humic acid; organic matter; manure; total glucosinolates